Individual Differences in Animal Stress Models: Considering Resilience, Vulnerability, and the Amygdala in Mediating the Effects of Stress and Conditioned Fear on Sleep - Wellman, Laurie L. (Sleep, 2016)
STUDY OBJECTIVES: To examine the REM sleep response to stress and fearful memories as a potential marker of stress resilience and vulnerability and to assess the role of the basolateral amygdala (BLA) in mediating the effects of fear memory on sleep. METHODS: Outbred Wistar rats were surgically implanted with electrodes for recording EEG and EMG and with bilateral guide cannulae directed at the BLA. Data loggers were placed intraperitoneally to record core body temperature. After recovery from surgery, the rats received shock training (ST: 20 footshocks, 0.8 mA, 0.5-s duration, 60-s interstimulus interval) and afterwards received microinjections of the GABAA agonist muscimol (MUS; 1.0 μM) to inactivate BLA or microinjections of vehicle (VEH) alone. Subsequently, the rats were separated into 4 groups (VEH-vulnerable (VEH-Vul; n = 14), VEH-resilient (VEH-Res; n = 13), MUS-vulnerable (MUS-Vul; n = 8), and MUS-resilient (MUS-Res; n = 11) based on whether or not REM was decreased, compared to baseline, during the first 4 h following ST. We then compared sleep, freezing, and the stress response (stress-induced hyperthermia, SIH) across groups to determine the effects of ST and fearful context re-exposure alone (CTX). RESULTS: REM was significantly reduced on the ST day in both VEH-Vul and MUS-Vul rats; however, post-ST MUS blocked the reduction in REM on the CTX day in the MUS-Vul group. The VEH-Res and MUS-Res rats showed similar levels of REM on both ST and CTX days. The effects of post-ST inactivation of BLA on freezing and SIH were minimal. CONCLUSIONS: Outbred Wistar rats can show significant individual differences in the effects of stress on REM that are mediated by BLA. These differences in REM can be independent of behavioral fear and the peripheral stress response, and may be an important biomarker of stress resilience and vulnerability. CITATION: Wellman LL, Fitzpatrick ME, Hallum OY, Sutton AM, Williams BL, Sanford LD. Individual differences in animal stress models: considering resilience, vulnerability, and the amygdala in mediating the effects of stress and conditioned fear on sleep. SLEEP 2016;39(6):1293–1303.